Adaptive Processes in the Respiratory System and Adrenals in Concomitant Brain Injury - D. V. Sundukov; V. I. Alisiyevich; A. M. Golubev; D. V. Taktayeva (Общая реаниматология)
Objective: to study the nature and time of development of pulmonary and adrenal structural changes in early concomitant brain injury. Materials and methods. The lungs and adrenals from 120 persons who had died from severe concomitant brain injury were morphologically studied. Pulmonary and adrenal specimens were embedded in paraffin. Histological sections were stained in hematoxylin-eosin, by using the procedures developed by Weigert, van Gieson, and Mallory. The Schick test and other histochemical methods were used. Morphometric studies were also employed. Statistical processing used Student’s t-test. Results. In injury, the early pulmonary structural changes were ascertained to be circulatory disorders, bronchial and bronchiolar mucosal damage, and the development of atelectases and focal emphysema. The morphological criteria for increased adrenal cortical functional activity are focal delipidization, diminished cortical transparency, the «spotty» appearance of the cortex, boundary-spanning between the cortical and reticular zones, multiple cytolysis, and iron plethora. Conclusion. Severe concomitant brain injury is followed by pulmonary structural changes underlying acute respiratory failure. Adrenal structural and functional changes play an important role in the pathogenesis of lung injury. Key words: severe concomitant brain injury, lung injury, adrenals.